2017
DOI: 10.26529/cepsj.365
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Preschool Teachers’ Beliefs about Foreign Language Learning and Early Foreign Language Teaching in Slovenia

Abstract: The implementation of foreign languages in preschool education has prompted the need for qualified teachers. However, most recent studies report a gap between the supply of qualified foreign language teachers of young learners and the demand for such teachers as foreign languages are introduced earlier and earlier. The authors of this paper present some models of initial and in-service training of preschool foreign language teachers in Slovenia. As learners’ beliefs about language learning have been considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
2
4
0
1
Order By: Relevance
“…Educationalists, on the other hand, were too much lesser degree in support of this decision as the results show that most of them were only in partial agreement with introducing English at this stage. These results are, to a large extent, in line with previous studies (e.g., Bago, 2008;Ogretir, 2008;Letica, 2009;Damar, Gursoy & Korkmaz, 2013: Habeeb, 2013Fojkar & Pizorn, 2015: see section 1.5.5 for more studies) reviewed in section two which show that parents teachers support the idea of teaching at an early stage. However, despite the fact that our findings are in line with existing relevant literature, the current findings are contradictory to Hwang's (1993) study, which showed that parents and teachers in Korea disagreed with teaching English at an early age as they thought it could have a negative effect on the pupils L1 among other things.…”
Section: Nosupporting
confidence: 90%
See 2 more Smart Citations
“…Educationalists, on the other hand, were too much lesser degree in support of this decision as the results show that most of them were only in partial agreement with introducing English at this stage. These results are, to a large extent, in line with previous studies (e.g., Bago, 2008;Ogretir, 2008;Letica, 2009;Damar, Gursoy & Korkmaz, 2013: Habeeb, 2013Fojkar & Pizorn, 2015: see section 1.5.5 for more studies) reviewed in section two which show that parents teachers support the idea of teaching at an early stage. However, despite the fact that our findings are in line with existing relevant literature, the current findings are contradictory to Hwang's (1993) study, which showed that parents and teachers in Korea disagreed with teaching English at an early age as they thought it could have a negative effect on the pupils L1 among other things.…”
Section: Nosupporting
confidence: 90%
“…Some people do support this decision believing that it is a positive step for the education system in Libya, whereas some others believe that it may be harmful to teach a foreign language at an early age, as was widely reported in many previous studies (e.g., Al-Thaferi, 1999;Al-Shammary, 1989) in which they claim that language should not be taught to young learners until they are adults and fully proficient in their first language. Moreover, many educationalists and specialists in Libya argue that in taking such a significant step and The Importance of Studying Teachers' and Parents' Perceptions towards Teaching English as a Foreign Language Teachers and parents are essential elements in the educational system, and studying their perceptions should be taken into consideration when implementing foreign language programs for young children because their perceptions are one of the aspects of constructing validity (Fojkar & Pizorn, 2014). Moreover, investigating the perceptions of parents is vital because of the influence they have on the formation of children's attitudes.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The emphasis on mastering the methodology is in line with the recommendations of Kelly et al (2004), Widlok et al (2010), or Vos (2008), who identify knowledge of methodology as a necessary basis for teaching English in kindergarten. The same opinion is obtained from students who identify methodology as the most important attribute of preparation for teaching English (Dagarin Fojkar & Skubic, 2017). Good knowledge of the methodology enables teachers to create learning opportunities appropriate to the age of the children and also to choose appropriate pedagogical strategies to achieve the set learning objectives.…”
Section: Discussionmentioning
confidence: 96%
“…VIO) slovenskih javnih osnovnih šol je bil povod mnogih razprav med praktiki in strokovnjaki, saj so se vsi zavedali posebnosti zgodnjega poučevanja tujih jezikov (TJ), kar predstavlja še dodaten izziv za predšolsko obdobje. V zadnjih dveh desetletjih je bilo opaziti bistveno povečano zanimanje za izide učenja in poučevanja tujih jezikov v najzgodnejšem obdobju, in sicer tako v Sloveniji (Čok, Skela, Kogoj in Razdevšek Pučko, 1999;Dagarin Fojkar in Skubic, 2017;Juriševič in Pižorn, 2013;Nagode in Pižorn, 2016; kot v tujini (Ellis, Brewster in Girard 2002;Enever, 2014;Hayes, 2014;. Od uradnega uvajanja prvega tujega jezika v 1.…”
Section: Sklepunclassified